THE STIMULATING MECHANISMS OF REGIONAL ECONOMIC ACTIVITY IN SPAIN: LESSOUS FOR RUSSIA - K. S. Seredinskaya (Vestnik MGIMO-Universiteta)
Spain is a country that traditionally suffers a lot from high level of regional disparities. From the end of XX century Spanish government has taken different measures to smooth them. For example, the state of autonomies was established, statutes were approved for every region, more powers were transferred to regional authorities. There are several institutions in Spain that increase the efficiency of cooperation between different levels of authorities and between autonomies, such as conference of the presidents, sectoral conferences, agreements on cooperation and bilateral commissions. Activity of these mechanisms is of a great interest for the author. The author tries to find the ways to modernize Russian regional policy using Spanish experience, considering its pros and cons. Undoubtedly it is impossible to copy other countries practice as Russia and Spain differ a lot, for example, in size, population, the level of socialeconomic development and the supply of mineral resources. Still there is something in common, like high level of regional disparities and amount of authorities the territories obtain. Even though Spain is a unitary state, its autonomies are quite independent. Territorial status of the country is a hybrid between unitary and federative state. Its institutional structure of regional policy is pretty diversified. So both these aspects are worth considering. Regional policy is one the most important directions of the state activity in Russia, because of its extensive territories. Today Russia has to face a number of regional challenges and regional policy cannot cope with them. The growing territorial polarization slow down the development of the whole country. It is useful to analyze foreign institutions, which solve regional problems in the other states, to adapt their practice to the Russian realities.